RANCANG BANGUN ALAT TERAPI ELEKTRIK UNTUK MEMBANTU PENYEMBUHAN CEDERA DI POLI FISIOTERAPI RSUD Dr SOEDOMO TRENGGALEK - Dwi Laila Qomarudin; Didik Riyanto; Jawwad Sulthon Habib (Universitas Muhammadiyah Ponorogo, 2021)
An injury is a disorder that occurs in the body which results in the appearance of redness, pain, swelling and the inability to function properly in the limbs. Handling of minor to severe injuries is carried out with medical treatment such as surgery or traditional medicine, but this treatment has not provided any assurance of healing, as for the alternative treatment, namely heat therapy. Heat therapy is able to open blood vessels wider and can provide a supply of oxygen and nutrients to reduce pain in injured sufferers. From this research, it can be produced a design of an electric therapy device that can produce heat equipped with a heat setting and a therapy time controller. The design of an electric therapy device to help heal physiotherapy dipole injuries at Dr. SOEDOMO Trenggalek Hospital has several advantages, namely that it can generate heat according to temperature settings, can adjust the length of therapy process time according to time settings and can also provide a display of temperature and time on the LCD display. The results of research on this electric therapy device are able to work according to predetermined working principles.